1996
DOI: 10.1016/1044-0305(95)00630-3
|View full text |Cite
|
Sign up to set email alerts
|

SiCl3+ and SiCl+ affinities for pyridines determined by using the kinetic method with multiple stage mass spectrometry: Agostic effects in the gas phase

Abstract: Cluster ions, Py1SiCl 3 (+) Py2 and Py1SiCl(+)Py2, where Py1 and Py2 represent substituted pyridines, formed upon reactive collisions of mass-selected SiCl 3 (+) or SiCl(+) cations with a mixture of pyridines, are shown to have loosely bound structures by multiple stage mass spectrometry experiments in a pentaquadrupole mass spectrometer. The fragment ion abundance ratio, ln([Py1SiCl n (+) ]/[Py2SiCl n (+) ]) (n=1 or 3) is used to estimate the relative SiCl 3 (+) or SiCl(+) affinities of the constituent pyridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…All optimized geometries are in excellent agreement with available experimental [1,2,51] and previously calculated [5,38,49,[51][52][53][54][55] values. The calculated E-X bond length is systematically longer in EX 3 2À/À than in EX 3 0/+ , and is consistent with the greater E-X bond polarity that is anticipated for an anion in which the E atom is in a lower formal oxidation state.…”
Section: Geometriessupporting
confidence: 83%
See 1 more Smart Citation
“…All optimized geometries are in excellent agreement with available experimental [1,2,51] and previously calculated [5,38,49,[51][52][53][54][55] values. The calculated E-X bond length is systematically longer in EX 3 2À/À than in EX 3 0/+ , and is consistent with the greater E-X bond polarity that is anticipated for an anion in which the E atom is in a lower formal oxidation state.…”
Section: Geometriessupporting
confidence: 83%
“…The gas-phase reaction of SiF 3 + with NH 3 in a SIFT apparatus led to HF elimination instead of stable complex formation [48]. The Lewis acidity of SiCl 3 + was demonstrated by tandem and multiple-stage mass spectrometry experiments using different substituted pyridines as the ligands which showed that SiCl 3 + Á2(pyr 1 pyr 2 ) adducts formed [49]. In view of the foregoing discussion, there is a need for a Lewis acidity scale that is independent of the nature of the donor ligand and free of the BSSE error.…”
Section: Introductionmentioning
confidence: 97%
“…45,46 The second point is emphasized by Drahos and Ve key,44 but also appears in the early experiments by McLuckey et al 45 Evidence for the third point has been discussed qualitatively in various recent experimental studies. 28,47 The elegant work of Drahos and Ve key44 enhances the understanding of e †ective temperature provided by Brauman and co-workers. 20 The latterÏs analysis indicates that Eqn (1) is most accurate when the cluster species is activated well above the average of the threshold energies for the two processes, that is, when the internal energy is high.…”
Section: Temperatures and Internal Energy Distributionsmentioning
confidence: 94%
“…Very recently, Reid, Roesky, Stalke, and their respective co‐workers synthesized the cationic chlorogermyliumylidene10a and chlorostannyliumylidene10b complexes B through a Lewis base mediated autoionization of GeCl 2 and SnCl 2 in the presence of a neutral tridentate donor ligand (Scheme ). In 1996, Cooks and co‐workers reported a mass spectrometry study of bis(pyridine)‐supported [ClSi:] + 9e. However, an isolable complex that bears the chlorosilyliumylidene cation is still unknown.…”
Section: Methodsmentioning
confidence: 99%